2021
DOI: 10.1016/j.cmi.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Early antibody response in health-care professionals after two doses of SARS-CoV-2 mRNA vaccine (BNT162b2)

Abstract: Objectives Data on the immune response after two doses of BNT162b2 are so far limited. Previously infected individuals were excluded from pivotal clinical trials and the optimal dose regimen in this population has not been clearly studied. The CRO-VAX HCP study aims at investigate the early antibody response in a population of healthcare professionals having received two doses of the BNT162b2 mRNA COVID-19 vaccine. Methods The CRO-VAX HCP study is a multicenter, prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 9 publications
9
42
0
Order By: Relevance
“…In a comparison of cancer patients to healthy controls after the first vaccination with BNT162b2, Monin-Aldama et al described rates of seroconversion of 97, 39, and 13% in healthy controls, solid cancer patients, and patients with hematological malignancies, respectively [26]. Indeed, high seroconversion rates of about 95% for healthy individuals after the first vaccination have been confirmed by others across different vaccine types, but with lower antibody titers in older individuals [27][28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…In a comparison of cancer patients to healthy controls after the first vaccination with BNT162b2, Monin-Aldama et al described rates of seroconversion of 97, 39, and 13% in healthy controls, solid cancer patients, and patients with hematological malignancies, respectively [26]. Indeed, high seroconversion rates of about 95% for healthy individuals after the first vaccination have been confirmed by others across different vaccine types, but with lower antibody titers in older individuals [27][28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…[3][4][5][6][7] Around the world, massive vaccination campaigns started in early 2021 and data about the immunological response emerged in the literature to document the evolution of humoral response in subjects vaccinated against SARS-CoV-2. [8][9][10][11][12][13][14][15] In the majority of seronegative subjects, antibody response was positive two weeks after the rst dose and the peak response was observed around 28 days. 13,16 The antibody titers were also higher in previously infected individuals compared to seronegative subjects and recent studies found a decline in antibody titers at 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] In the majority of seronegative subjects, antibody response was positive two weeks after the rst dose and the peak response was observed around 28 days. 13,16 The antibody titers were also higher in previously infected individuals compared to seronegative subjects and recent studies found a decline in antibody titers at 3 months. 13,17−19 This antibody decline needs to be well-monitored because it may provide important information to support the decision-making on the potential use of a booster dose.…”
Section: Introductionmentioning
confidence: 99%
“…While most available data of BNT162b2 vaccine are on antibodies elicited upon the first vaccine dose in healthy or SARS-CoV-2 previously infected subjects or at early time points following the second dose (18)(19)(20)(21)(22)(23)(24), our study profiling the antibody response and memory B cells up to six months after vaccination contributes to better understand the BNT162b2 vaccine immunogenicity in SARS-CoV-2 naive subjects.…”
Section: Discussionmentioning
confidence: 99%